1974
DOI: 10.1037/h0036059
|View full text |Cite
|
Sign up to set email alerts
|

The reactivity and unreliability of self-recording.

Abstract: Several therapeutic strategies in behavior modification require subjects to selfobserve and to self-record their own behavior. Self-recording appears to be reactive, with the phenomenon having two components: actual changes in behavior as a function of self-recording and possible unreliability of selfobservers. The present study was undertaken to differentially examine the reactivity and reliability of self-observations; a second purpose was to assess the role of awareness of reliability estimates in the relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
3

Year Published

1977
1977
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(30 citation statements)
references
References 17 publications
1
26
0
3
Order By: Relevance
“…Self-management research suggests that the act of observing oneself often alters the behavior observed (Lipinski & Nelson 1974). This "selfmonitoring effect" is additionally noteworthy in that change typically occurs in a desired direction (Johnson & White 1971;McFall 1970).…”
Section: Scrutinizing Selfmentioning
confidence: 99%
“…Self-management research suggests that the act of observing oneself often alters the behavior observed (Lipinski & Nelson 1974). This "selfmonitoring effect" is additionally noteworthy in that change typically occurs in a desired direction (Johnson & White 1971;McFall 1970).…”
Section: Scrutinizing Selfmentioning
confidence: 99%
“…The results reported by different authors (Broden, Hall, & Mitts, 1971;Hayes & Cavior, 1977;Lipinski & Nelson, 1974) show the reactivity is manifest even when self-monitoring has low reliability. The unreliability of self-monitoring, as well as its reactivity, may render difficult the use of self-monitoring as an assessment tool, but as Nelson ( 1978) pointed out, we still have to identify the mechanisms by which self-monitoring changes behavior.…”
Section: Self-monitoringmentioning
confidence: 77%
“…The suggested reactivity of self‐monitoring usually is minimized by extending the baseline assessment up to at least 2 weeks [7]. In the literature, two types of possible biases are discussed: the validity of subjective self‐reports is questioned in terms of the increased accuracy of the estimates during self‐monitoring via sleep logs (‘instrumental’ bias) [3, 9]; the second type is related to the therapeutic effects that are induced by self‐monitoring per se (‘therapeutic’ bias) [4, 6], an effect that is discussed not only in relation to sleep logs.…”
Section: Introductionmentioning
confidence: 99%